Multi-unit turns that begin with a resaying of a prior speaker's turn - Skogmyr Marian, Klara; Malabarba, Taiane; Weatherall, Ann (My University, 2021)
This study examines the interactional workings of multi-unit turns that have an initial turn-constructional unit that re-says the immediately prior single-unit turn produced by another speaker. Based on cases in English, Portuguese, and French, our analysis shows that resayings do confirming and also 1) index the speaker's rights over the propositional component of the words, and 2) support the extension of the turn. In addition to confirming, resayings thus claim rights to what has been said and demonstrate an entitlement to say more. The resayings thereby have both a retrospective and prospective function, the latter being closely related to turn-taking management. Our findings contribute to the existing literature on other-repeats by considering what these do in a multi-unit turn environment.